Desarrollo y evaluación de la elaboración de una sopa instantánea a partir del arroz de cebada (Hordeumvulgare) tostada y sin tostar con dos concentraciones de harina (quinua (Chenopudiumquinowilld)y trigo (Triticumaestivum)), y dos saborizantes artificiales (res y pollo) en “cereales la pradera” en el período 2012 - Alpusig Paste, María Fernanda (2013)
The objective of this research was to develop the production of instant soup rice from barley (Hordeum vulgare) roasted and unroasted with two concentrations of flour (quinoa and wheat) and two concentrations of artificial flavors (beef and chicken) in "Cereals La Pradera"located in the province of Cotopaxi, Latacunga canton, parish Belisario Quevedo. We performed various transformations of grain from a classification, milled, polished, pre-cooking, cut and toast the final product as barley rice. Proximate analysis of unroasted barley rice resulted: Protein (8.35%) Fat (1.40%) Carbohydrates (68.6%). While roasted barley rice was: protein (9.13%) Fat (1.05%) Carbohydrates (68.7%). From the presentations obtained from barley rice, developed a formula with ingredients and additives allowed in food consumption. Acceptability was evaluated soups organoleptic attributes obtained with the help of semi-trained judges. The ingredients for instant soup were 70% rice + barley flour (quinoa or wheat) 3% + flavor (beef or chicken) 3% + 24% other ingredients (salt, onion powder, garlic powder, corn starch , milk and dried cilantro)….